Perlindungan Hukum Kreditur Terhadap Intervensi Kreditur Dengan Jaminan Hak Tanggungan Yang Sama - Karina Dwi Maharani; Rafiqa Sari (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Legal protection is very important in credit agreements, especially for lenders/creditors (creditors). Legal protection is all forms of efforts to protect respect and recognition of human dignity and human rights in the field of law. Credit is generally used to facilitate business and plays a very important role in Indonesia's economic activities. Its position applies to both manufacturing companies and private companies which are developed independently because it aims to improve the people's standard of living. As a financial institution that provides financial services, banks play a role in economic activities by providing credit through bank loans and other means in the form of credit agreements between creditors who are lenders, or lines of credit with obligors who are debtors who have helped meet funding needs. The problem is about the form of legal protection for creditors if the debtor defaults and what sanctions are imposed by the creditor if the debtor defaults. The results obtained from this legal research are a form of legal protection given to creditors when the debtor defaults according to Law Number 4 of 1996, namely a credit agreement set forth in the form of a deed, either in the form of an underhand deed or an authentic deed in accordance with the Elucidation of Article 10 of the Law -Law No. 4 of 1996, that by issuing a Mortgage Letter by the Land Office as proof of the existence of a Mortgage which is irah-irah and has the same executor power as a judge's decision which has permanent legal force, then if the debtor defaults or defaults, he can ask for help directly to the Head of the local District Court to carry out the execution through a public auction in order to obtain payment of creditors' receivables. As well as the interpretation in Law Number 4 of 1996 which provides legal protection to creditors, namely the provisions of Article 1 number 1 concerning creditor preference rights; Article 6, Article 14 paragraphs (1), (2), and (3) and Article 20 paragraphs (2) and (3) concerning the implementation of Mortgage Rights; Article 11 paragraph (2) regarding promises that must be included in the Deed of Granting Mortgage Rights (APHT) to protect creditors if the debtor defaults, as well as the provisions of Article 7 concerning the principle of droit de suite which states that mortgage rights still guarantee objects even though they are transferred to third parties so that they remain guarantee the payment of creditors' receivables.